2017
DOI: 10.1016/j.neuroimage.2016.08.067
|View full text |Cite
|
Sign up to set email alerts
|

Acute stress increases risky decisions and dampens prefrontal activation among adolescent boys

Abstract: Adolescence is characterized by increased risky decision-making, enhanced mesolimbic response to risk and reward, increased perceived stress, and heightened physiological response to stress relative to other age groups. In adults, evidence suggests that acute stress increases risky decision-making by stress-induced increases of dopamine in regions implicated in reward processing and decision-making. Acute stress also increases risky decision-making in adolescents, but the underlying neurobiological mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 63 publications
2
31
0
Order By: Relevance
“…Using a within-subjects daily diary approach to measuring daily stress and an adaptive risky decision-making task, we showed that SLEEP AND STRESS ON RISKY DECISIONS 5 adolescent males (15-17 years) took more advantageous risks under high relative to low stress whereas adult males (25-30 years) took fewer non-advantageous (equal expected value) risks under high relative to low stress. Moreover, despite showing similar sensitivity to expected value, adolescent males demonstrated increased overall risk preference under high stress relative to adult males while there were no differences in risky decisions under low stress conditions (Uy & Galván, 2016). These developmental differences in stress-related risky behaviors were paralleled by developmental differences in stress-related functional activation in the PFC during adaptive risky decision-makingsuch that adolescent males evinced reduced PFC activation during high relative to low stress when making advantageous decisions (relative to disadvantageous decisions) whereas adult males showed no stress-related changes in PFC recruitment (Uy & Galván, 2016).…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Using a within-subjects daily diary approach to measuring daily stress and an adaptive risky decision-making task, we showed that SLEEP AND STRESS ON RISKY DECISIONS 5 adolescent males (15-17 years) took more advantageous risks under high relative to low stress whereas adult males (25-30 years) took fewer non-advantageous (equal expected value) risks under high relative to low stress. Moreover, despite showing similar sensitivity to expected value, adolescent males demonstrated increased overall risk preference under high stress relative to adult males while there were no differences in risky decisions under low stress conditions (Uy & Galván, 2016). These developmental differences in stress-related risky behaviors were paralleled by developmental differences in stress-related functional activation in the PFC during adaptive risky decision-makingsuch that adolescent males evinced reduced PFC activation during high relative to low stress when making advantageous decisions (relative to disadvantageous decisions) whereas adult males showed no stress-related changes in PFC recruitment (Uy & Galván, 2016).…”
mentioning
confidence: 84%
“…Moreover, despite showing similar sensitivity to expected value, adolescent males demonstrated increased overall risk preference under high stress relative to adult males while there were no differences in risky decisions under low stress conditions (Uy & Galván, 2016). These developmental differences in stress-related risky behaviors were paralleled by developmental differences in stress-related functional activation in the PFC during adaptive risky decision-makingsuch that adolescent males evinced reduced PFC activation during high relative to low stress when making advantageous decisions (relative to disadvantageous decisions) whereas adult males showed no stress-related changes in PFC recruitment (Uy & Galván, 2016). Moreover, decreasing PFC activation under stress was related to greater non-advantageous risks under stress, suggesting that the developing PFC may be more sensitive to the effects of stress.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Along those lines, conflict intensity between parents and adolescents also increases in adolescence, and, at its extreme, is associated with adverse youth outcomes, including depression and risk behaviors (Laursen et al 1998;Weymouth et al 2016). While the mechanism of this association remains unclear, experiencing acute stress, such as conflictual interactions with parents, may affect adolescents' decision-making for risk behaviors (Galvan and Rahdar 2013;Uy and Galvan 2017). In the current study, we sought to investigate how the experience of parent-adolescent conflict impacts adolescent risk-taking, using behavioral and physiological indicators of arousal and self-regulation, respectively.…”
mentioning
confidence: 99%
“…In the current study, we sought to investigate how the experience of parent-adolescent conflict impacts adolescent risk-taking, using behavioral and physiological indicators of arousal and self-regulation, respectively. Understanding how parentadolescent conflict is related to risk-taking is essential because the experience of social stress may potentiate the already-existing heightened risk for adverse outcomes in adolescence (Uy and Galvan 2017).…”
mentioning
confidence: 99%